The Relationship Between Foreign Teachers’ Perception of Leadership Styles and Motivation at Assumption College Bangrak Campus, Bangkok - Kistenfeger, Stephan; Vinitwatanakhun, Watana (Scholar: Human Sciences, 2018)
: The main purpose of this study was to investigate the possible relationship between foreign teachers’ perception of leadership styles and motivation at Assumption College Bangrak Campus, in which 51 foreign teachers participated. For the 3 research objectives a quantitative study was used with the following purpose: (1) To investigate foreign teachers’ perception on the leadership style of the administrator of Assumption College Bangrak Campus. (2) To investigate foreign teachers’ perception on their own motivation at Assumption College Bangrak Campus. (3) To investigate if a significant relationship between foreign teachers’ perception on the leadership style of the administrator of Assumption College Bangrak Campus and their own motivation exist. The main research instrument consisted of 44 different research questions, which were adapted from Johnson’s study on employee motivation (1997), and from Indvik’s study on the path-goal theory (1985). The results showed that (1) the leadership style of the administrator of Assumption College Bangrak Campus is perceived to be supportive leadership by the majority of foreign teachers, (2) the majority of foreign teachers perceive their own motivation to be the need to fulfill esteem needs first and (3) there is a significant relationship between foreign teachers’ perception on the leadership style of the administrator of Assumption College Bangrak Campus and their own motivation.